Full-biodegradable polyester resin and biological lignin composite thermal shrinkage film as well as preparation method and application thereof
By modifying enzymatic lignin and fully biodegradable polyester resin as raw materials to prepare composite heat shrink films, the problem of lack of degradable heat shrink films in the prior art is solved, and the high mechanical strength, biodegradation rate and antibacterial properties of the material are achieved, and it is suitable for tobacco packaging and other fields.
Patent Information
- Application Number
- CN202510109163.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-18
AI Technical Summary
There is a lack of relevant reports in the prior art on the preparation of degradable heat shrinkable films using enzymatic lignin, resulting in technical gaps in this field.
The modified enzymatic lignin and fully biodegradable polyester resin are used as raw materials to prepare composite heat shrink films. The mechanical strength and biodegradability of the material are improved by the preparation method of modified enzymatic lignin and the preparation process of composite heat shrink films.
The composite heat shrink film of fully biodegradable polyester resin and biolignin has excellent mechanical strength, biodegradation rate and antibacterial properties, and avoids the problem of poor transparency, meeting the packaging requirements in the tobacco field.
Smart Images

Figure BDA0005256250980000011 
Figure BDA0005256250980000021 
Figure BDA0005256250980000061
Abstract
Description
Technical Field
[0001] The present application belongs to the field of material technology, and specifically relates to a composite heat shrinkable film of fully biodegradable polyester resin and biological lignin, and a preparation method and application thereof. Background Art
[0002] As an efficient and flexible packaging material, heat shrink film is widely used in food, beverage, industry and other fields due to its unique properties. Traditional heat shrink film is made of polymer materials such as PVC, PE, POF, etc. These materials are difficult to degrade in the natural environment and will pose a potential threat to the environment if they exist for a long time. With the strengthening of people's environmental awareness and the advancement of technology, environmentally friendly and sustainable degradable heat shrink film has become a popular research direction.
[0003] Lignin, as the second largest degradable natural polymer in the world, is widely present in plants and has good biocompatibility, degradability and no cytotoxicity. Enzymatic lignin is a new type of lignin separated from the residue of microbial enzymatic hydrolysis of corn stalks to prepare butanol and other energy sources. Compared with traditional alkali lignin and sulfate lignin, enzymatic lignin has multiple active groups and good reaction activity, and has been widely used. For example, the prior art CN113278265A uses enzymatic lignin to prepare agricultural mulch film, the prior art CN119144126A uses enzymatic lignin and PBAT to prepare a composite material suitable for cling film and mulch film, and the prior art CN103232579A provides a transparent ultraviolet absorption film material prepared with enzymatic lignin. However, there is no relevant report or prior art on the preparation of degradable heat shrink film with enzymatic lignin as raw material.
[0004] Therefore, a new type of biodegradable heat shrinkable film is needed to fill the technical gap in the field of preparing degradable heat shrinkable film by enzymatic hydrolysis of lignin. Summary of the invention
[0005] The problem that the present application aims to solve is to provide a composite heat shrinkable film of fully biodegradable polyester resin and biological lignin, and a preparation method and application thereof. The composite heat shrinkable film uses modified enzymatic lignin and fully biodegradable polyester resin as raw materials, has excellent mechanical strength and biodegradation rate, and provides a new utilization direction for biomass by-product lignin.
[0006] In order to solve the above technical problems, this application adopts the following technical solutions:
[0007] On the one hand, the present application provides a composite heat shrinkable film of a fully biodegradable polyester resin and bio-lignin, comprising, by weight:
[0008]
[0009]
[0010] Wherein, the modified biological lignin includes modified enzymatic lignin.
[0011] Furthermore, the preparation method of the modified enzymatically hydrolyzed lignin comprises:
[0012] The enzymatically hydrolyzed lignin is dried and then ground for the first time, and then sieved to obtain biological lignin powder; anhydrous N'N-dimethylformamide is added to the biological lignin powder, stirred and dissolved to obtain a biological lignin solution; formaldehyde is added to the biological lignin solution, and then the pH is adjusted to 11 using a NaOH solution. After reacting for 3 to 4 hours, an HCl solution is added to adjust the pH to 3, and a precipitate is collected after centrifugation. The precipitate is washed, dried, and ground for the second time to obtain the modified enzymatically hydrolyzed lignin powder.
[0013] Furthermore, the solid-liquid ratio of the bio-lignin powder to the anhydrous N'N-dimethylformamide is 1:(5-9).
[0014] Furthermore, the weight ratio of the bio-lignin solution to the formaldehyde is 1:(3-5).
[0015] Furthermore, the fully biodegradable polyester resin includes polybutylene glycol succinate.
[0016] Furthermore, the opening agent includes EBS.
[0017] Furthermore, the chain extender includes ADR-4368.
[0018] Furthermore, the lubricant includes zinc stearate.
[0019] Furthermore, the thermal stabilizer includes calcium sulfate whiskers.
[0020] Furthermore, the antioxidant includes antioxidant 1076.
[0021] Furthermore, the organic nucleating agent includes an amide organic nucleating agent or a hydrazide organic nucleating agent.
[0022] Furthermore, the filler masterbatch includes corn flour and talcum powder.
[0023] Furthermore, the weight ratio of the corn flour to the talcum powder is (1-3):1.
[0024] On the other hand, the present application provides a method for preparing the above-mentioned composite heat shrinkable film, comprising the following steps:
[0025] The fully biodegradable polyester resin and the modified bio-lignin powder are dried, mixed with the opening agent, the chain extender, the lubricant, the heat stabilizer, the antioxidant, the organic nucleating agent and the filler masterbatch, extruded and cooled to obtain a cast sheet; the cast sheet is biaxially stretched and rolled and slit to obtain the composite heat shrinkable film.
[0026] Furthermore, the mixing is carried out in a twin-screw extruder, the aspect ratio of the twin-screw extruder is 40:1, the barrel temperature of the twin-screw extruder is 165°C in the first section, 170°C in the second section, 175°C in the third section, 180°C in the fourth section, 175°C in the fifth section, and 165°C in the sixth section, and the rotation speed of the twin-screw extruder is 80-90r / min.
[0027] Furthermore, the temperature of the biaxial stretching is 80-90° C., the transverse stretching of the biaxial stretching is 3 times, and the longitudinal stretching of the biaxial stretching is 2 times.
[0028] On the other hand, the present application provides the use of the above-mentioned composite heat shrinkable film or the composite heat shrinkable film prepared by the above-mentioned method in tobacco packaging.
[0029] This application has the following beneficial effects:
[0030] (1) The modified enzymatic lignin used in the present application can effectively overcome the inhibitory effect of the phenolic hydroxyl groups in the lignin structure on the free radical reaction.
[0031] (2) The present application uses modified enzymatically hydrolyzed lignin and fully biodegradable polyester resin as raw materials to produce a composite heat shrinkable film, which not only maintains the flexibility of the fully biodegradable polyester resin, but also utilizes lignin to improve the mechanical strength, antibacterial properties and biodegradability of the heat shrinkable film.
[0032] (3) Lignin itself is brown in color due to the presence of a variety of chromophores and auxochrome groups. Direct use in the preparation of heat shrinkable films can easily lead to poor transparency. The use of modified enzymatically hydrolyzed lignin in this application can effectively avoid the poor transparency of the composite heat shrinkable film. In addition, the use of an organic nucleating agent in this application can further improve the transparency of the composite heat shrinkable film.
[0033] (4) The preparation process of the composite heat shrinkable film of the present application is simple, the raw materials are cheap and environmentally friendly, and the development and utilization of lignin is realized. DETAILED DESCRIPTION
[0034] The technical solutions in some embodiments of the present disclosure are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments provided by the present disclosure, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present disclosure.
[0035] Example 1
[0036] The modified enzymatic lignin was prepared according to the following steps:
[0037] S11. The enzymatically hydrolyzed lignin is dried and first ground, passed through a 120-mesh sieve, and the sieved powder is collected to obtain a biological lignin powder;
[0038] S12. Add 5 parts of anhydrous N'N-dimethylformamide to 1 part of the bio-lignin powder, stir and dissolve to obtain a bio-lignin solution;
[0039] S13. Add 3 parts of formaldehyde to 1 part of the bio-lignin solution, then use NaOH solution to adjust the pH to 11, react for 3 hours, add HCl solution to adjust the pH to 3, collect the precipitate after centrifugation at 800 rpm for 5 minutes, wash, dry and grind the precipitate for a second time to obtain the modified enzymatic lignin.
[0040] Example 2
[0041] The modified enzymatic lignin was prepared according to the following steps:
[0042] S11. The enzymatically hydrolyzed lignin is dried and first ground, passed through a 120-mesh sieve, and the sieved powder is collected to obtain a biological lignin powder;
[0043] S12. Add 7 parts of anhydrous N'N-dimethylformamide to 1 part of the bio-lignin powder, stir and dissolve to obtain a bio-lignin solution;
[0044] S13. Add 4 parts of formaldehyde to 1 part of the bio-lignin solution, then use NaOH solution to adjust the pH to 11, react for 3 hours, add HCl solution to adjust the pH to 3, collect the precipitate after centrifugation at 800 rpm for 5 minutes, wash, dry and grind the precipitate for a second time to obtain the modified enzymatic lignin.
[0045] Example 3
[0046] The modified enzymatic lignin was prepared according to the following steps:
[0047] S11. The enzymatically hydrolyzed lignin is dried and first ground, passed through a 120-mesh sieve, and the sieved powder is collected to obtain a biological lignin powder;
[0048] S12. Add 9 parts of anhydrous N'N-dimethylformamide to 1 part of the bio-lignin powder and stir to dissolve to obtain a bio-lignin solution;
[0049] S13. Add 5 parts of formaldehyde to 1 part of the bio-lignin solution, then use NaOH solution to adjust the pH to 11, react for 3 hours, add HCl solution to adjust the pH to 3, collect the precipitate after centrifugation at 800 rpm for 5 minutes, wash, dry and grind the precipitate for a second time to obtain the modified enzymatic lignin.
[0050] Example 4
[0051] Follow these steps to prepare the filler masterbatch:
[0052] S21. Mix 1 part of corn flour and 1 part of talcum powder to obtain the filling masterbatch.
[0053] Example 5
[0054] Follow these steps to prepare the filler masterbatch:
[0055] S21. Mix 2 parts of corn flour and 1 part of talcum powder to obtain the filling masterbatch.
[0056] Example 6
[0057] Follow these steps to prepare the filler masterbatch:
[0058] S21. Mix 3 parts of corn flour and 1 part of talcum powder to obtain the filling masterbatch.
[0059] Example 7
[0060] The composite heat shrinkable film of fully biodegradable polyester resin and bio-lignin was prepared according to the following steps:
[0061] S31. After drying, 90 parts of polybutylene glycol succinate and 20 parts of the modified enzymatic lignin powder prepared in Example 1 are added to a twin-screw extruder with a barrel temperature of 165°C for one section, 170°C for two sections, 175°C for three sections, 180°C for four sections, 175°C for five sections, and 165°C for six sections, and an aspect ratio of 40:1, and mixed and extruded at 80 r / min, and cooled by a rotary drum to obtain a cast sheet;
[0062] S32. The cast sheet is stretched 3 times in the transverse direction and 2 times in the longitudinal direction at 80° C., and then rolled up and slit to obtain a composite heat shrinkable film of the fully biodegradable polyester resin and bio-lignin.
[0063] Example 8
[0064] The composite heat shrinkable film of fully biodegradable polyester resin and bio-lignin was prepared according to the following steps:
[0065] S31. After drying, 95 parts of polybutylene glycol succinate and 30 parts of the modified enzymatic lignin powder prepared in Example 2 were added to a twin-screw extruder with a barrel temperature of 165°C for one section, 170°C for two sections, 175°C for three sections, 180°C for four sections, 175°C for five sections, and 165°C for six sections, and an aspect ratio of 40:1, and mixed and extruded at 85 r / min, and cooled by a rotary drum to obtain a cast sheet;
[0066] S32. The cast sheet is stretched 3 times in the transverse direction and 2 times in the longitudinal direction at 85° C., and then rolled up and slit to obtain the composite heat shrinkable film of the fully biodegradable polyester resin and bio-lignin.
[0067] Example 9
[0068] The composite heat shrinkable film of fully biodegradable polyester resin and bio-lignin was prepared according to the following steps:
[0069] S31. After drying, 100 parts of polybutylene glycol succinate and 40 parts of the modified enzymatic lignin powder prepared in Example 3 were added to a twin-screw extruder with a barrel temperature of 165°C for one section, 170°C for two sections, 175°C for three sections, 180°C for four sections, 175°C for five sections, and 165°C for six sections, and the length-to-diameter ratio was 40:1, and the mixture was extruded at 90 r / min, and then cooled by a rotary drum to obtain a cast sheet;
[0070] S32. The cast sheet is stretched 3 times in the transverse direction and 2 times in the longitudinal direction at 90° C., and then rolled up and slit to obtain the composite heat shrinkable film of the fully biodegradable polyester resin and bio-lignin.
[0071] Comparative Example 1
[0072] The method for preparing the heat shrinkable film in this comparative example is referenced to Example 7; wherein, the difference between Comparative Example 1 and Example 7 is only that:
[0073] In S31, the modified enzymatically hydrolyzed lignin is replaced with lignin.
[0074] Comparative Example 2
[0075] The method for preparing the heat shrinkable film in this comparative example is referenced to Example 7; wherein, the difference between Comparative Example 2 and Example 7 is only that:
[0076] In S31, the amide organic nucleating agent is replaced by nano-SiO2.
[0077] Comparative Example 3
[0078] Follow these steps to prepare the heat shrink film:
[0079] S41. After drying, 90 parts of polybutylene glycol succinate were mixed with 0.5 parts of EBS, 0.5 parts of ADR-4368, 0.6 parts of zinc stearate, 0.1 parts of calcium sulfate whiskers, 0.2 parts of antioxidant 1076, 5 parts of amide organic nucleating agent and 15 parts of the filler masterbatch prepared in Example 4. The barrel temperature was 165 ° C for one section, 170 ° C for two sections, 175 ° C for three sections, 180 ° C for four sections, 175 ° C for five sections, and 165 ° C for six sections. The aspect ratio was 40: 1 and the extruder was mixed at 80 r / min and extruded, and cooled by a drum to obtain a cast sheet;
[0080] S42. The cast sheet is stretched 3 times in the transverse direction and 2 times in the longitudinal direction at 80°C, and then rolled up and slit to obtain the heat shrinkable film.
[0081] Example 1
[0082] In order to verify the performance of the composite heat shrink film of the fully biodegradable polyester resin and bio-lignin of the present application, the inventors conducted a series of research experiments. After testing, the performance of the heat shrink film obtained in Examples 7 to 9 and Comparative Examples 1 to 3 is shown in Table 1
[0083] Table 1
[0084]
[0085] According to Table 1, it can be seen that the composite heat shrinkable film made by using modified enzymatic lignin and fully biodegradable polyester resin as raw materials in the present application effectively improves the mechanical strength and flexibility of the heat shrinkable film, and successfully overcomes the influence of the color of lignin on the transparency of the heat shrinkable film material, and can meet the packaging requirements in the tobacco field; in addition, when preparing Example 7 and Comparative Example 1, it was also found that the product yield of Comparative Example 1 was much lower than that of Example 7. Combined with the use of formaldehyde to modify lignin in the present application, it can be shown that the present application effectively overcomes the inhibitory effect of phenolic hydroxyl groups in lignin on free radical reactions.
[0086] Experimental Example 2
[0087] In order to further verify the biodegradation rate, biosafety and antibacterial property of the composite heat shrinkable film of the fully biodegradable polyester resin and bio-lignin of the present application, the inventor conducted a series of research experiments. After testing, the biodegradation rate, biosafety and antibacterial property of the composite heat shrinkable film of the fully biodegradable polyester resin and bio-lignin obtained in Examples 7 to 9 and Comparative Examples 1 to 3 are shown in Table 2.
[0088] Table 2:
[0089]
[0090] It can be seen from Table 2 that the composite heat shrinkable film of fully biodegradable polyester resin and bio-lignin provided in the present application has excellent biodegradability, no heavy metals are detected, and has good biological toxicity and antibacterial properties. It will not cause any impact on the human body or the environment after use, and can be applied to multiple fields in the future.
[0091] The above is only a preferred embodiment of the present disclosure. It should be understood that the present disclosure is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not deviate from the spirit and scope of the present disclosure, and should be within the scope of protection of the claims attached to the present disclosure.
Claims
1. A composite heat shrinkable film of fully biodegradable polyester resin and bio-lignin, characterized in that: In parts by weight: Wherein, the modified biological lignin includes modified enzymatic lignin.
2. The composite heat shrinkable film according to claim 1, characterized in that: The preparation method of the modified enzymatic lignin comprises: The enzymatically hydrolyzed lignin is dried and then first ground and then sieved to obtain biological lignin powder; Adding anhydrous N'N-dimethylformamide to the bio-lignin powder and stirring to dissolve the bio-lignin solution; Formaldehyde is added to the bio-lignin solution, and then the pH is adjusted to 11 using a NaOH solution. After reacting for 3 to 4 hours, an HCl solution is added to adjust the pH to 3. The precipitate is collected after centrifugation, and the precipitate is washed, dried, and ground for a second time to obtain the modified enzymatic lignin powder.
3. The composite heat shrinkable film according to claim 2, characterized in that: The solid-to-liquid ratio of the bio-lignin powder to the anhydrous N'N-dimethylformamide is 1:(5-9); And / or, the weight ratio of the bio-lignin solution to the formaldehyde is 1:(3-5).
4. The composite heat shrinkable film according to claim 1, characterized in that: The fully biodegradable polyester resin includes polybutylene glycol succinate; And / or, the opening agent includes EBS; and / or, the chain extender comprises ADR-4368; and / or, the lubricant comprises zinc stearate; and / or, the heat stabilizer comprises calcium sulfate whiskers; and / or, the antioxidant comprises antioxidant 1076; And / or, the organic nucleating agent includes an amide organic nucleating agent or a hydrazide organic nucleating agent; And / or, the filler masterbatch comprises corn flour and talc.
5. The composite heat shrinkable film according to claim 4, characterized in that: The weight ratio of the corn flour to the talcum powder is (1-3):
1.
6. A method for preparing a composite heat shrinkable film according to any one of claims 1 to 5, characterized in that: The following steps are involved: The fully biodegradable polyester resin and the modified bio-lignin powder are dried, mixed with the opening agent, the chain extender, the lubricant, the heat stabilizer, the antioxidant, the organic nucleating agent and the filler masterbatch, extruded and cooled to obtain a casting sheet; The cast sheet is subjected to biaxial stretching, winding and slitting to obtain the composite heat shrinkable film.
7. The method according to claim 6, characterized in that: The mixing is carried out in a twin-screw extruder, the aspect ratio of the twin-screw extruder is 40:1, the barrel temperature of the twin-screw extruder is 165°C in the first section, 170°C in the second section, 175°C in the third section, 180°C in the fourth section, 175°C in the fifth section, and 165°C in the sixth section, and the rotation speed of the twin-screw extruder is 80-90r / min; And / or, the temperature of the biaxial stretching is 80-90° C., the transverse stretching of the biaxial stretching is 3 times, and the longitudinal stretching of the biaxial stretching is 2 times.
8. Use of the composite heat shrinkable film according to any one of claims 1 to 5 or the composite heat shrinkable film prepared by the method according to any one of claims 6 to 7 in tobacco packaging.
Citation Information
Patent Citations
Method of preparing transparent ultraviolet absorption membrane material from enzymatic hydrolysis lignin
CN103232579A
Degradable lignin-based composite agricultural mulching film and preparation method thereof
CN113278265A
Enzymatic hydrolysis lignin PBAT composite material, degradable film and preparation method of degradable film
CN119144126A